Cardioprotective effect of fasting on ischemia reperfused rat heart after diazepam administration. - Shackebaei, Dareuosh; Nasri, Sima; Kalaee, Soheila Ebrahimi Vosta; Miankouhi, Mitra Azadi; Hesari, Mahvash (International Cardiovascular Research Journal, 2012)
Background: Fasting and calorie restriction have some cardioprotective effects. In view of the effect of fasting on peripheral benzodiazepine receptors and widespread administration of benzodiazepines in medicine, the present study was designed to evaluate whether fasting may affect myocardial vulnerability to cardiac ischemiaDSreperfusion (I/R) following repeated diazepam administration. Methods: Rats were divided into six groups of 8 or 10 animals. Groups I and II were controls which received intra peritoneal injection of normal saline solution for 5 days. Also, Control II underwent fasting on 5th day of experiment. Four test groups received intra peritoneal injection of diazepam for 5 days (groups I and II 1mg/kg; groups III and IV 5 mg/kg). Also, test groups II and IV fasted on 5th day of experiment. The Langendorff isolated hearts were subjected to 25 minutes ischemia and 25 minutes reperfusion. Cardiac parameters including left ventricular developed pressure and rate pressure product were determined. Infarct size was measured by Triphenyltetrazolium staining. Results: Recovery of the left ventricular developed pressure in diazepam groups were significantly lower than control I and II (P=0.049 and P=0.046 respectively). But there was no significant difference among the controls and test group II, which fasted following diazepam administration. This showed the preservation of the cardiac performance in the fasting animals following administration of diazepam (1 mg/kg). Conclusion: The results obtained showed the exacerbation of ischemia reperfusion injury in the presence of diazepam and demonstrated the protective effect of fasting which is probably due to modulation of the mitochondrial permeability transition pore.